Psydrax multiflora sp. nov. (Rubiaceae) from Palawan, Philippines. (5th January 2017) - Arriola, Axel H.; Cobangkiat, Adrienne B.; Alejandro, Grecebio Jonathan D.
Abstract : Psydrax multiflora, a new species of Vanguerieae collected in the Palawan, Luzon Island, Philippines is herein described and illustrated. Morphological observation showed that P. multilfora approaches three Malesian Psydrax species, namely P. amplifolia, P. nitida and P. puberula . However, P. multiflora can be delineated from these three by its caudate leaf apex, 20–30‐flowered umbellate inflorescences and broadly triangular corolla lobes.